APPLICATION OF THE FORWARD RECURSIVE EQUATION MODEL ON WASTE TRANSPORTATION ROUTES IN MEDAN JOHOR DISTRICT USING DYNAMIC PROGRAMMING ALGHORITHM - Hanum, Syarifah; Azura, Maudya Nur; Sari, Dinda Permata; Husein, Ismail (Pena Cendekia Insani, 2024)
Waste problems often occur in big cities such as Jakarta, Surabaya, Medan, Bandung, Yogyakarta and Semarang. Urban waste is waste produced by human activities in urban areas, including various types of materials such as plastic, paper, metal and organic materials. Therefore, waste needs to be collected, transported and disposed of immediately to prevent negative impacts on the environment. With the increase in population in urban areas, it is likely that the amount of waste will also increase. The solution that can be used to solve this problem is to optimize the distance using a dynamic programming model forward recursive equation algorithm. The application of dynamic programming can be used to solve various problems such as determining the shortest distance, optimal flow, task or resource scheduling, production planning, network optimization, and problems in research and development projects. Based on determining the optimal route for transporting waste in Medan Johor District using the dynamic programming algorithm forward recursive equation model, the total distance is 26,2km.